If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -65.375 = 7.2(9c + 1) Reorder the terms: -65.375 = 7.2(1 + 9c) -65.375 = (1 * 7.2 + 9c * 7.2) -65.375 = (7.2 + 64.8c) Solving -65.375 = 7.2 + 64.8c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-64.8c' to each side of the equation. -65.375 + -64.8c = 7.2 + 64.8c + -64.8c Combine like terms: 64.8c + -64.8c = 0.0 -65.375 + -64.8c = 7.2 + 0.0 -65.375 + -64.8c = 7.2 Add '65.375' to each side of the equation. -65.375 + 65.375 + -64.8c = 7.2 + 65.375 Combine like terms: -65.375 + 65.375 = 0.000 0.000 + -64.8c = 7.2 + 65.375 -64.8c = 7.2 + 65.375 Combine like terms: 7.2 + 65.375 = 72.575 -64.8c = 72.575 Divide each side by '-64.8'. c = -1.119984568 Simplifying c = -1.119984568
| (2x+9)+(2x+8)+(2x)=(2x)+(3x+1) | | 2a/3+1/5 | | 7/3x+9/6x=36/9 | | 10y=12.6 | | -3a+4=-8 | | 6(3x-2)=18x-12 | | 4x^2+19x+22=0 | | 35=45 | | (-2/7)(2m+6)=(1/28)m-11 | | x+15+2x=-5-2x-30 | | -14-4(x)=-58 | | 6(2x+6)= | | 8y+3(y-5)=6(y+1)-3 | | 40/x-40x+39=0 | | 2(3x-6)+5=12-(x+5) | | r-3/7r=98000 | | (8x^2-3x^3)-(5x^2-9x^3)= | | 4556776+455556= | | 4.2+10m=6.75 | | (1/4)d-(2/5)=(3/4)d+11 | | 10=a-7 | | x^2-(6x)=13 | | 7x+2x(x+6)=39 | | x+5.2=-6.5 | | 15(p^2-1)-16p=0 | | -4=-7x | | 0.1+1.4=1.2x-3 | | 10x+18=4x+60 | | 17/2y=-17 | | 8+3(s-6t)= | | x^2y^4z/(x^2y)3*(x^10y^5z^4)^2/y^3z^2 | | 3(8+3/2y)+4y=7 |